HERDSMEN ATTACKS IN NIGERIA’S SOUTHEAST AND THE DIALECTICS OF STATE BEHAVIOUR - ONYEKWELU, Ebuka; ONYEKWELU, Ginika; BIEREENU-NNABUGWU, Makodi (Socialscientia: Journal of Social Sciences and Humanities, 2020)
The Southeast of Nigeria have witnessed one form of herdsmen attack or the other in recent times. This paper interrogates the emerging trend of adverse herdsmen activities in the five Southeast states of Abia, Anambra, Ebonyi, Enugu and Imo. What is the nature or pattern of adverse herdsmen activities in the region and to what extent do their activities constitute trespasses and violent invasions? Using the instruments of key informant interview (KII) and select case situations, the study examines the specific patterns of interface between adverse herdsmen activities, southeast communities and state behaviour in relation to trespasses and violent invasions of communities. Our findings suggest that herdsmen operate as if they are above the laws in Nigeria; and that the state in Nigeria, particularly the instrumentality of governance appears to show no serious interest in curbing herdsmen excesses by forestalling their attacks, and ensuring that justice prevails for the victims of attacked communities in the region.